AN ANALYSIS OF TEACHER PEDAGOGICAL MISCONDUCT IN TEACHING ENGLISH - Hardiansah Sinurat; Siti Aisah Ginting; Safrida Lubis (Universitas Negeri Medan, 2020)
This study was aimed to find out the types of teacher pedagogical misconduct and the reasons of teacher pedagogical misconduct. The research was conducted by using descriptive qualitative. The data were the result of questionnaire and interviewing of English teacher at SMP Swasta Josua Medan. The data were analyzed based on types of teacher pedagogical misconduct by Kearney and reason of teacher pedagogical misconduct by Riley and Lewis. The findings showed that there were three types of teacher pedagogical misconduct. They were indolence, incompetence, and offensiveness. Moreover, the dominant category of indolence is changing assignments every time, while failure to treat student properly is in incompetence and involving sarcasm in offensiveness. The teacher conducted pedagogical misconduct due to treat students differently, teaching in sharp sarcasm technique, restricted, releasing anger and hardly braid good relationship.Keywords: teacher pedagogical misconduct, teaching English